2020
DOI: 10.1101/2020.09.17.301044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Quorum Sensing Peptide EntF* Promotes Colorectal Cancer Metastasis in Mice: A New Factor in the Microbiome-Host Interaction

Abstract: BackgroundColorectal cancer, one of the most common malignancies worldwide, is associated with a high mortality rate, mainly caused by metastasis. Comparative metagenome-wide analyses between healthy individuals and cancer patients suggest a role for the human intestinal microbiota. Nevertheless, which microbial molecules are involved in this communication is largely unknown, with current studies mainly focusing on short chain fatty acids and amino acid metabolites as potential mediators. However, quorum sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Regarding other quorum sensing peptides, one report mentions the presence of a thiolacton peptide without compelling evidence via mass spectrometry [54]. Recently, Debunne et al provided proof on the in vivo presence of a specific quorum sensing peptide metabolite, in other words, EntF*, linked to E. faecium [55] and Streptococci quorum sensing peptides have been found in the human oral cavity [56]. Another report strongly indicated the presence of the quorum sensing peptide PapRIV, produced by Bacillus cereus strains, in mouse plasma [57].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other quorum sensing peptides, one report mentions the presence of a thiolacton peptide without compelling evidence via mass spectrometry [54]. Recently, Debunne et al provided proof on the in vivo presence of a specific quorum sensing peptide metabolite, in other words, EntF*, linked to E. faecium [55] and Streptococci quorum sensing peptides have been found in the human oral cavity [56]. Another report strongly indicated the presence of the quorum sensing peptide PapRIV, produced by Bacillus cereus strains, in mouse plasma [57].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Debunne et al demonstrated the in vivo presence of a quorum sensing peptide metabolite in blood, i.e. EntF* [13].…”
Section: Introductionmentioning
confidence: 99%